The implementation of nu-oriented learning based on moral akhlaq values: A case study at mts nu 02 gringsing, batang regency - Nur Koyin; Joko Widodo; Ifada Retno Ekaningrum (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines the implementation of Ke-NU-an learning based on moral values at MTs NU 02 Gringsing, Batang Regency, as a model of character education grounded in the values of Ahlussunnah wal Jama’ah (Aswaja). The background of this research is the growing moral crisis among students, which necessitates educational approaches that emphasize value internalization and character formation. Employing a qualitative descriptive approach, this field research collected data through interviews, participant observation, and documentation involving teachers, students, and school administrators. The findings reveal that Ke-NU-an learning has been systematically integrated into both instructional and non-instructional activities, including religious habituation programs, extracurricular activities, and daily school culture. The implementation of Aswaja values such as moderation, tolerance, balance, and responsibility contributes significantly to the development of students’ religious character, discipline, social awareness, and appreciation of local culture. Furthermore, the role of teachers as moral role models and the institutional support provided by the school strengthen the effectiveness of character education. This study concludes that Ke-NU-an learning grounded in moral values functions not only as religious instruction but also as a strategic framework for character education in Islamic secondary schools under the auspices of Nahdlatul Ulama.